Cardiovascular magnetic resonance in patients with mitral valve prolapse - Stefano Figliozzi; Silvana Di Maio; Georgios Georgiopoulos; Bert Vandenberk; Amedeo Chiribiri; Marco Francone; Nay Aung; Steffen E. Petersen; Tim Leiner; Jan Bogaert; Pier-Giorgio Masci (Journal of Cardiovascular Magnetic Resonance)
ABSTRACT: With a prevalence of 2–3% in the general population, mitral valve prolapse (MVP) is the most common valvular heart disease. The clinical course is benign in the majority of patients, although severe mitral regurgitation, heart failure, and sudden cardiac death affect a non-negligible subset of patients. Imaging of MVP was confined to echocardiography until a few years ago when it became apparent that cardiovascular magnetic resonance (CMR) could offer comparative advantages for detecting and quantifying mitral valve abnormalities alongside tissue myocardial characterization. The present review highlights the growing body of evidence supporting the role of CMR in patients with MVP. Based on the recent literature, CMR appears not as a simple alternative to echocardiography in patients with poor acoustic windows, but as a complementary imaging modality instrumental for better quantifying mitral valve abnormalities, mitral regurgitation severity, ventricular remodeling, and myocardial tissue changes. In this respect, pivotal CMR studies highlight that mitral annular disjunction and myocardial fibrosis by late gadolinium enhancement are associated with a heightened risk of life-threatening ventricular arrhythmias (arrhythmic MVP). We also delineate how these and other markers (e.g., the severity of mitral regurgitation) could enable a personalized risk assessment in patients with MVP and implement clinical decision-making. Here, we provide a comprehensive review of the current literature, with an emphasis on the arrhythmic MVP phenotype. The review also provides some practical suggestions on how to carry out a dedicated CMR protocol in MVP and composes a thorough report to inform clinicians on key aspects of this valvular heart disease.